The Development of Braille Scrabble Enhancing English Vocabulary Acquisition among Visually Impaired Students in Secondary Education - Rena Tri Setyo Maryana; Nur Azizah (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The mastery of English vocabulary among visually impaired students is significantly hindered by a heavy reliance on audio-based assistive technology, which often fails to reinforce structural spelling and orthographic understanding. This reliance creates a persistent literacy gap that affects their overall language proficiency. This study aims to develop a multisensory Scrabble Braille learning media and to evaluate its feasibility, practicality, and effectiveness in enhancing vocabulary acquisition for secondary students. Following the Research and Development (R&D) approach with the ADDIE model, the research was conducted at SMK N 8 Surakarta and MAN 2 Sleman, involving six visually impaired participants. Data were collected through expert validation, pretests, posttests, and user questionnaires. Results indicate that the media is highly feasible, with material and media validation scores reaching 97.5% and 93.75%, respectively. Practicality tests conducted by teachers and students yielded "Very Good" ratings, highlighting ease of use and increased motivation. Furthermore, the media proved effective as average student scores rose significantly from 4.83 to 8.33. This innovation provides an inclusive, dual-access solution that bridges the literacy gap between visually impaired and sighted learners while fostering independent learning.